PENGARUH ARUS KAS DAN KEBIJAKAN DEVIDEN TERHADAP HARGA SAHAM DI BURSA EFEK INDONESIA - Rizal, Rahma (JURNAL MANAJEMEN DAN AKUNTANSI, 2014)
The secondari Market is veri important for investor to know as information as cash flow, and dividend policy and stock prices. This study aimed to determine the effect of cash flow and dividend policy on stock prices either simultaneously or partially. This study uses purposive sampling method in the selection of the sample and study period consisted of 7 days which is 3 days before and after the publication of the financial statements. The statistical methods used to test the hypothesis is multiple linear regression. The results showed that simultaneous cash flow, and dividend policy affect stock prices. However, partial results show that only cash flow investing negatively affect while dividend policy has no effect on stock prices. Keywords: stock price, cash flow, and dividend policy